Peningkatan Efisiensi Penggunaan Sumber Daya Jaringan Melalui Teknik Load Balancing - Khoiru Sabila; Siti Rahayu; Titin Sumarni (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research explores increasing the efficiency of network resource use through load balancing techniques. Load balancing distributes workload evenly among servers to optimize resource usage, maximize throughput, and minimize response time. We compare various load balancing algorithms, such as round-robin, least connections, and least response time, in various network scenarios. Experimental results show that proper load balancing techniques can reduce response time by up to 30% and increase resource usage efficiency by up to 40%. This study highlights the importance of selecting appropriate algorithms based on network traffic and workload characteristics. Implementing effective load balancing strategies can improve the quality of network services and ensure even distribution of workloads, providing practical guidance for network administrators to optimize network performance and efficiency.